Scientific Signs in Surah Ar-Rahman According to Tantawi Jawhari's Perspective in Tafsir al-Jawahir - Jamil, Mhd. Khoirudin; Zuhri, Ahmad; Harahap, Mardian Idris (Universitas Islam Negeri Raden Intan Lampung, 2024)
The Qur'an, as the holy book of Muslims, contains scientific signs that direct humans to reflect on natural phenomena as signs of the greatness of Allah SWT. Surah Ar-Rahman, one of the surahs rich in scientific signs, invites humans to explore science and understand the universe through a scientific approach. In this context, Tantawi Jawhari, through Tafsir al-Jawahir, stands out as an interpreter with a scientific approach that connects the verses of the Qur'an with the discoveries of modern science, showing that divine revelation and science complement each other. This study is a qualitative study with a descriptive-analytical nature that uses a hermeneutic and contextual approach with data sources originating from the book Tafsir al-Jawahir and supporting literature, which are processed through the stages of identification, classification, and thematic interpretation of verses containing scientific signs with content and contextual analysis methods used to draw conclusions systematically and comprehensively. These findings confirm that Surah Ar-Rahman not only provides spiritual guidance but also offers scientific insights that encourage humans to be grateful, maintain the balance of nature, and utilize science wisely. This study concludes that the Qur'an and science complement each other, providing guidelines for a harmonious and sustainable life.